2004
DOI: 10.1523/jneurosci.4161-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neuronal Phenotypes from Neural Progenitor Cells

Abstract: We report the first isolation of progenitor cells from the hypothalamus, a derivative of the embryonic basal plate that does not exhibit neurogenesis postnatally. Neurons derived from hypothalamic progenitor cells were compared with those derived from progenitor cultures of hippocampus, an embryonic alar plate derivative that continues to support neurogenesis in vivo into adulthood. Aside from their different embryonic origins and their different neurogenic potential in vivo, these brain regions were chosen be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 62 publications
7
99
2
1
Order By: Relevance
“…5e,f). Both early-and late-passage neurospheres differentiated after growth factor reduction, as assessed by the presence of RIP þ ive oligodendrocytes 34 , GFAP þ cells with astrocytic morphology 35 , TUJ1 þ ve immature neurons 36,37 and growth hormone releasing hormone (GHRH) þ ive hypothalamic neurons 32 (Fig. 5g).…”
Section: Resultsmentioning
confidence: 99%
“…5e,f). Both early-and late-passage neurospheres differentiated after growth factor reduction, as assessed by the presence of RIP þ ive oligodendrocytes 34 , GFAP þ cells with astrocytic morphology 35 , TUJ1 þ ve immature neurons 36,37 and growth hormone releasing hormone (GHRH) þ ive hypothalamic neurons 32 (Fig. 5g).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a study in 1996 and additional ones later on reported that cells surrounding the third ventricle could generate neurospheres (Weiss et al 1996;Xu et al 2005;Li et al 2012;Robins et al 2013) and monolayer cell culture generating neurons and glia (Markakis et al 2004). Based on 24-h post-BrdU experiments, proliferative cells have been identified in both the parenchyma and along the third ventricle (for a review, see Migaud et al 2010).…”
Section: Adult Neurogenesis In the Hypothalamus: Parenchymal Or Germimentioning
confidence: 99%
“…Moreover, a recent study has shown that the TRH peptide is present in adult hippocampal NSPCs 122 , suggesting that TRH may affect these cells in a paracrine or autocrine manner.…”
Section: Thyrotropin-releasing Hormonementioning
confidence: 99%
“…Interestingly, a recent study has shown that the TRH peptide is present in adult hippocampal stem/progenitor cells 122 . This suggests that TRH may act as an autocrine or paracrine modulator of NSPC proliferation.…”
Section: Trh Stimulates Proliferation In Nspcsmentioning
confidence: 99%